The Impact of AI on Literary Analysis: Opportunities and Challenges (International Journal of Scientific Research in Science and Technology, 2024)
In today’s world, artificial intelligence is revolutionizing a wide range of fields by becoming an essential tool which people highly rely on. One significant application of AI is text interpretation where AI tools are used to summarize, interpret, explore, review, analyze, and so on. This development gives rise to critical questions about the role of AI in shaping human understanding of literary works. This paper aims to explore the intersection of AI and literature by examining whether machine-generated interpretations exhibit true creativity or it is reflecting biased opinions towards dominant cultures. AI has the potential to aid in education but minimal interaction with information can foster creativity instead of promoting active interpretation that might lead to plagiarism or lack of originality. Furthermore, people become more reliant on AI driven interpretations so there is a concern that human creativity may be overshadowed or replaced by machine creativity. Instead of complementing, AI is slowly narrowing our own human perspectives without our awareness. This paper suggests that AI should play a supportive role, enhancing human creativity and learning rather than contributing to plagiarized content.